(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The implementation of tectonic expression within Indonesian architecture has undergone a marked reduction in recent times. This decline is especially discernible in vernacular structures such as the Rumoh Aceh. As a significant element of cultural heritage, Rumoh Aceh embodies distinctive formal configurations and spatial principles that merit investigation through a tectonic lens. The principal aim of this study is to examine the applicability of the shape grammar method in analyzing the tectonic characteristics inherent in the form of Rumoh Aceh. Employing an explanatory case study as its methodological framework, this research entails a thorough examination of pertinent literature related to the application of shape grammar. The analytical findings indicate that the shape grammar methodology can be effectively utilized to codify the architectural form and tectonic elements of Rumoh Aceh. This methodological approach is anticipated to enrich the spectrum of techniques available for exploring and recording tectonic knowledge within the context of traditional Indonesian architecture, with a concentrated emphasis on Rumoh Aceh.